시민사회단체에서 아카이브를 만든다는 것: '1997 외환위기 아카이브' 구축 사례 - 김조은; Kim, Joeun (Journal of Records Management & Archives Society of Korea, 2020)
This paper introduces the process in which the Center for Freedom of Information, founded for the public's right to know by disseminating public information, was created <Archives of 1997 Korean Financial Crisis>. Building archives with scarce resources and capacities has resulted in a number of troubles and frustrations, and the need for reorientation. However, through the contributions of many people empathizing with the unique needs and meanings of citizen-led archives, difficulties were overcome, and archives were built. This paper summarizes the specific difficulties and capabilities required in this process, especially the knowledge and assistance needed in the field of records management. Although much research is necessary, the archives serve as an example of remembering and reconstructing the past when the 1997 Crisis Archives had shaken all the foundations of people's lives, and a tool to guide decision-making. 본 논문은 "공공정보의 대중화를 통해 시민의 알 권리를 실현하고 사회 전반의 투명성과 책임성을 높여나가는 것을 목적"으로 설립된 시민사회 단체인 '투명사회를 위한 정보공개센터'에서 <1997 외환위기 아카이브>를 만든 과정을 소개한다. 소규모 시민사회 단체에서도 충분히 주제 아카이브를 만들 수 있다는 다소 낙관적인 판단에서 작업을 시작했으나, 부족한 자원과 역량으로 아카이브를 구축하면서 많은 좌충우돌과 좌절, 그에 따른 방향의 수정이 거듭되었다. 하지만 시민이 주도하는 아카이브 고유의 필요와 의미에 공감하는 많은 사람들의 기여를 통해 난관을 극복하고 아카이브를 구축할 수 있었다. 논문에서는 구축 과정에 대한 소개와 함께 구체적인 어려움과 필요했던 역량들이 무엇인지, 특히 기록관리 분야에서 어떤 지식과 도움이 필요했는지 정리하였다. 아직 이용자 수는 2천명 남짓이지만 <1997 외환위기 아카이브>가 우리 삶의 토대를 흔들었던 과거를 우리 스스로의 힘으로 기억하고 재구성하는 좋은 사례로서, 그리고 더 나은 결정들에 조금이나마 보탬이 되는 도구로서 오래 기능하기를 바란다.